Correspondence and cluster analysis of free-drawn clocks in a group of children and adolescents with neurological and psychiatric diseases. Issue 1 (2nd January 2018) - Kaczmarek, Izabela; Kleka, Paweł; Fliciński, Piotr; Steinborn, Barbara
ABSTRACT: The present work addresses the identification and qualitative assessment of errors that appear in a free-drawn clock-drawing test representing the time 8:20 in a sample of 455 children and adolescents with neurological diseases and their controls. The authors sought to verify whether the occurrence of particular errors in the clock drawings significantly differentiates the clinical groups. For statistical evaluation of the results, we applied correspondence analysis and cluster analysis. The results of the study showed that three types of errors played an important role in the differentiation of the groups: spatial neglect, mirror reflection, and phonological depletion.